PEMANFAATAN SISA PANEN TANAMAN PISANG SEBAGAI PENGGANTI RUMPUT DALAM PAKAN KOMPLIT BERBENTUK PELET TERHADAP PERFORMANS DOMBA LOKAL JANTAN LEPAS SAPIH - Benny Syah Braymana (Universitas Sumatera Utara, 2014)
The research was conducted in the Animal Biology Laboratory, Animal Husbandry Department, Agriculture Faculty, University of Sumatera Utara started from July to November 2013. This aims of research was to determine utilization of pelleting banana crop residu to substitute grass on feed intake, body weight gain and feed conversion ratio of weaning male local sheep. Twenty male local sheeps were used with initial body weight 8,63±2,06 kg/head and divided into four treatments and five replications using completely randomized design as design experiment. The treatments were analyzed level substitution of grass with banana crop residu i;e 0% (P0), 33% (P1), 67% (P2), 100% (P3). Variables were observed consist of feed intake, body weight gain and feed conversion ratio. The results showed that utilization of pelleting banana crop residu to substitute grass were not significantly different effect (P>0,05) on feed intake, body weight gain and feed conversion ratio. Feed intake (g/head/day) for treatments P0; P1; P2; P3 were 325,32; 369,24; 369,91; 345,36, respetively, while for body weight gain (g/head/day) were 39,45; 51,24; 59,70; 55,32, and for feed conversion ratio 11,74; 7,63; 6,32; 7,11, respectively. It is concluded that pelleting banana crop residu could substitute grass as much as 100%.Keywords : Performance, Weaning male local sheep, Banana crop residu